Keefektifan Metode Talking Stick Berbantu Media Youtube Dalam Pembelajaran Menceritakan Kembali Teks Deskriptif Pakaian Adat Jawa Pada Siswa Kelas XII SMAN 2 Blora Tahun Ajaran 2022-2023 - Fauziah, Laily Hanum; Zaidah, Nuning; Sulanjari, Bambang (Universitas PGRI Semarang, 2022)
This research was motivated by students who still looked passive, limited choice of words, lacked confidence in conveying ideas and ideas so that learning activities became less effective. This is because one of the factors in the selection of methods and media in learning that is less varied causes a lack of enthusiasm for learning by students. The problem in this research is how effective the talking stick method with the help of youtube media is in learning descriptive text of Javanese traditional clothes for class XII students of SMA N 2 Blora for the 2022-2023 academic year. The purpose of this study is to describe the effectiveness of the talking stick method assisted by youtube media in learning descriptive text of Javanese traditional clothes for class XII students of SMA N 2 Blora, 2022-2023 academic year. This research is a pre-experimental design research that uses a one-shot case study research design. The data collection technique in this study is a test in the form of performance and non-test obtained through observation (observation) and questionnaires (questionnaire). Furthermore, the data were analyzed by means of descriptive statistics. The population and sample in this study were purposive sampling.The results of the study based on the results of data analysis are as follows: in the knowledge aspect there are 29 students who have completed with a percentage of 83% and there are 6 students who have not completed with a percentage of 17%. In the aspect of skills, there are 32 students who have completed with a percentage of 91% and there are 3 students who have not completed with a percentage of 9%. These results in terms of knowledge and skills aspects can be categorized as effective because more than 50% of students are able to achieve completeness scores compared to the specified KKM value. The conclusion of the research using the talking stick method with the help of YouTube media in learning to retell descriptive text about Javanese traditional clothes is feasible and effective to use because it has an influence on the learning process.Â